2010
DOI: 10.1073/pnas.1010249107
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of IL-7 receptor and T-cell receptor signaling by cell-division cycle 42 in T-cell homeostasis

Abstract: T-cell homeostasis is essential for normal functioning of the immune system. IL-7 receptor (IL-7R) and T-cell receptor (TCR) signaling are pivotal for T-cell homeostatic regulation. The detailed mechanisms regulating T-cell homeostasis and how IL-7R and TCR signaling are coordinated are largely unknown. Here we demonstrate that T cell-specific deletion of cell-division cycle 42 ( Cdc42 ) GTPase causes a profound loss of mature T cells. Deletion of Cdc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 51 publications
4
70
0
Order By: Relevance
“…So far, an autoregulatory role for Gfi1 as well as a transregulatory role for Gfi1b has been documented (53). Also, downstream signaling of the GTPase Cdc42 has been proposed to suppress Gfi1 expression in resting T cells (54). The current study now proposes that glucocorticoids are a new family of molecules that can control Gfi1 expression.…”
Section: Discussionmentioning
confidence: 71%
“…So far, an autoregulatory role for Gfi1 as well as a transregulatory role for Gfi1b has been documented (53). Also, downstream signaling of the GTPase Cdc42 has been proposed to suppress Gfi1 expression in resting T cells (54). The current study now proposes that glucocorticoids are a new family of molecules that can control Gfi1 expression.…”
Section: Discussionmentioning
confidence: 71%
“…We tested the function of Cdc42 in Tregs because it had been previously shown that T cell-specific deletion of Cdc42 resulted in decreased T cell trafficking and cell survival (31). As expected, the number of Tregs was drastically decreased in lungs of Foxp3…”
Section: Creert2mentioning
confidence: 88%
“…20 As such, WASp is classically involved in actin rearrangement processes at the cell leading edge leading to membrane protrusions. WASp also controls podosome assembly and integrindependent adhesion, and is implicated in cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…20 To determine WASp and PAK binding, National Institutes of Health (NIH) 3T3 cells overexpressing HA3-tagged-Cdc42S71P were subjected to the pull-down assay using the Cdc42 effector probe, GST-WASp or GST-PAK, as previously described. 20 MxCre Tg/ϩ ;WT and MxCre Tg/ϩ ; Cdc42 flox/flox bone marrow cells were transduced with retroviral supernatant. 10,21 EGFP ϩ cells were isolated and transplanted into lethally irradiated C57Bl/6 animals.…”
Section: Retroviral Transduction Of Mutant Vectorsmentioning
confidence: 99%